A Better Wound Care Assessment on Burn Patients - Sanjaya, Hendra; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2012)
Backgrounds: Burn, a damage and tissue loss caused by heat with a high morbidity and mortality, have a many variation and complex problem that require special management. After a period of shock, there were infections that threaten the burn patients. These hazards aggravate the wound to become wider, and it affects the mortality and the length of stay. That is why to reduce mortality rate and length of stay, we need a proper wound care.Methods:A retrospective descriptive studies was perform on 2b degree burn patients (20-25%) that treated with tangential excision and mebo or tangential excision and stsg. Data was taken from burns unit Cipto Mangunkusumo hospital in period of January to December 2011.Results: There were 30 patients (73.2%) that have been treat with tangential excision and mebo, and 11 patients (26.8%) that have been treat with tangential excision and stsg. The average length of stay for the tangential excision and mebo is 22.47 ? 23 days(SD 4.361), whereas patients with tangential excision and stsg is 15.82 ?16 days (SD 2.089). There were 8 patients (26.7%) with tangential excision and mebo that die, whereas patients with tangential excision and stsg were 2 patients (18.2%) that die. There were significant difference in the average length of stay (p = 0.018), but there was no difference in the proportion of patients dying status (P = 0.611).Conclusion:Wound care by tangential excision and stsg on 2b degree burn patient (20-25%), have a better outcome than patients treated by tangential excision and mebo.